2013
DOI: 10.1167/iovs.12-10916
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Iris Mechanics on the Pupillary Light Reflex Using Brimonidine-Induced Anisocoria

Abstract: Iris mechanics limits the amount of pupil contraction and can act to reduce the assessed neuronal integration of the pupil light reflex. Pupil response assessed by using percent contraction amplitude is least affected by mechanical effects and provides a more accurate approximation of afferent input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The effect was similar to that reported in other studies [29, 30]. On the other hand, other studies reported that the antimydriatic effect of brimonidine was pronounced under both light and dark luminance conditions [3134]. Therefore, the application of brimonidine 20 min before activities in dimly lit areas or at night may be recommended for photic phenomena following laser refractive surgery [35].…”
Section: Discussionsupporting
confidence: 86%
“…The effect was similar to that reported in other studies [29, 30]. On the other hand, other studies reported that the antimydriatic effect of brimonidine was pronounced under both light and dark luminance conditions [3134]. Therefore, the application of brimonidine 20 min before activities in dimly lit areas or at night may be recommended for photic phenomena following laser refractive surgery [35].…”
Section: Discussionsupporting
confidence: 86%
“…The effect of brimonidine ophthalmic solution (0.1-0.2%) on the melanopsin-mediated PIPR Late remains uninvestigated, while other topical antiglaucomatous drugs such as dorzolamide, latanoprost and timolol do not affect the melanopsin-mediated PIPR Late (Ba-Ali et al 2015). Nonetheless, despite anisocoria, Chen & Kardon (2013). found no difference in the transient PLR between the brimonidine-treated eyes compared to the fellow untreated eyes when stimulated with red light.…”
Section: Discussionmentioning
confidence: 99%
“…). Nonetheless, despite anisocoria, Chen & Kardon (). found no difference in the transient PLR between the brimonidine‐treated eyes compared to the fellow untreated eyes when stimulated with red light.…”
Section: Discussionmentioning
confidence: 99%
“…Such variability could also be due to mechanical effects of small pupil size on iris movement. 63 We used a closed-loop paradigm, such that PLR was measured in the same eye that received the light stimulation; hence, retinal illumination was affected by baseline pupil size. To minimize the influence of pupil size, an open-loop paradigm could be used in which one pupil is dilated pharmacologically and stimulated with light but recordings are taken from the undilated contralateral eye.…”
Section: Discussionmentioning
confidence: 99%